Editing Aspergillus terreus using the CRISPR-Cas9 system. Issue 1 (6th December 2022) - Shih, Sra-Yh; Mortensen, Uffe Hasbro; Chang, Fang-Rong; Tsai, HsinYuan
Abstract: CRISPR-Cas9 technology has been utilized in different organisms for targeted mutagenesis, offering a fast, precise and cheap approach to speed up molecular breeding and study of gene function. Until now, many researchers have established the demonstration of applying the CRISPR/Cas9 system to various fungal model species. However, there are very few guidelines available for CRISPR/Cas9 genome editing in Aspergillus terreus . In this study, we present CRISPR/Cas9 genome editing in A. terreus . To optimize the guide ribonucleic acid (gRNA) expression, we constructed a modified single-guide ribonucleic acid (sgRNA)/Cas9 expression plasmid. By co-transforming an sgRNA/Cas9 expression plasmid along with maker-free donor deoxyribonucleic acid (DNA), we precisely disrupted the lovB and lovR genes, respectively, and created targeted gene insertion ( lovF gene) and iterative gene editing in A. terreus ( lovF and lovR genes). Furthermore, co-delivering two sgRNA/Cas9 expression plasmids resulted in precise gene deletion (with donor DNA) in the ku70 and pyrG genes, respectively, and efficient removal of the DNA between the two gRNA targeting sites (no donor DNA) in the pyrG gene. Our results showed that the CRISPR/Cas9 system is a powerful tool for precise genome editing in A. terreus, and our approach provides a great potential for manipulating targeted genes and contributions to gene functional study of A. terreus . Graphical Abstract: